Positive psychology school‐based interventions: A reflection on current success and future directions. Issue 1 (30th August 2016) - Chodkiewicz, Alicia R; Boyle, Christopher
Abstract : An increased focus on youth development has led to an understanding of the importance of the wellbeing, resilience and mental health of children and young people. As a result there is a growing body of research, especially over the last two decades, which increasingly recognises the complexities of learning and development across the years spent at school. Alongside this trend is the rise of positive psychology, which is changing our conceptions of youth, education and development. Support for a new era of student‐centric teaching practices dedicated to enhancing student wellbeing has come not only from researchers and psychologists, but also from school and education authorities, who are showing an increased appetite for integrating positive psychology‐based programs into the learning curriculum. While researchers are beginning to express cautious optimism about the effectiveness of such interventions, there is a large disparity between the initiatives being researched and what is being taught in classrooms. A set of key constraints relating to limited resources, an overcrowded curriculum, accessibility of information, teacher factors and quality training all play a role in shaping the effectiveness with which an intervention is implemented. This article reflects on the recent development of positive psychology school‐based programs and offers insights into how these initiatives can be enhanced to reach a wider range of young people and translated more effectively into classroom practice.